Problems in Defining Leadership – A Systematic Literature Review - Bugaj, Justyna; Sulyma, Alla (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: The paper offers an analysis and definition of the concept of leadership in the light of current socio-economic trends. The following research questions were posed: “How is leadership understood?” and “What elements comprise its definition?”. The definitions of leadership place the term in a range of categories: as a characteristic, a behaviour, a process, a role relationship, or a position in an organisational structure. It has been analysed through multiple paradigms, including classical, transactional, transformational, situational, and service leadership. It is not clear at present which definition is dominant, nor which research methods have been used to determine its constituent elements. Research Design & Methods: A critical and systematic literature review covering publications that appeared in the years 2010–2020; 55 full-text indexed publications were analysed from the Scopus database. Findings: The research draws together and organises definitions of leadership that have appeared in the last 10 years in the publications indexed from the Scopus database. The authors also put forward their own definition of leadership from the perspective of management and quality sciences. Implications / Recommendations: Organising the definition of leadership allows the authors to understand the diversity and complexity which have a positive impact on building, strengthening and developing leadership. The study also brings to light areas and directions for further research, e.g. in the gender of managers or discrepancies in the perception of leadership resulting from publications from various geographic and cultural regions. Contribution: Arranging the existing definitions of leadership and its components from the perspective of management and quality sciences; demonstrating that a qualitative approach is increasingly used in leadership research.